From 3D hydrodynamic simulations of common-envelope interaction to gravitational-wave mergers - Moreno, Melvin M.; Schneider, Fabian; Röpke, Friedrich; Ohlmann, Sebastian T.; Pakmor, Rüdiger; Podsiadlowski, Philipp; Sand, Christian (Arxiv, 2021)
Modeling the evolution of progenitors of gravitational-wave merger events in binary stars faces two major uncertainties: the common-envelope phase and supernova kicks. These two processes are critical for the final orbital configuration of double compact-object systems with neutron stars and black holes. Predictive one-dimensional models of common-envelope interaction are lacking and multidimensional simulations are challenged by the vast range of relevant spatial and temporal scales. Here, we present three-dimensional hydrodynamic simulations of the common-envelope interaction of an initially 10 M⊙ red supergiant primary star with a black-hole and a neutron-star companion. ...